ANALISIS IMPLEMENTASI PROGRAM PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS DI SDLB NEGERI PRABUMULIH - Annisa Putri; Jayanti Jayanti; Ali Fakhrudin (JS (JURNAL SEKOLAH), 2022)
Abstract:. Education is a very important need for every human being, the state has an obligation to provide the right to education without exception, including those who have differences in abilities (disabled). The purpose of this research is to analyze the implementation of the education program for children with special needs (ABK), this study uses descriptive qualitative methods, data collection uses observation, interviews and documentation techniques, from the results of research conducted at SDLB Negeri Prabumulih, there are several types of children with special needs. With special needs (ABK) which have different classifications, the teacher conducts an assessment every semester to identify children with special needs (ABK). This school uses the 2013 curriculum and a special curriculum when needed, the learning process in the classroom is not much different from other public schools, it's just that sometimes teachers have to be more patient in dealing with students with disabilities (different or abnormal abilities).Keywords: Analysis, Learning Poses, ABK Abstrak: Pendidikan merupakan kebutuhan yang sangat penting bagi setiap manusia negara memiliki kewajiban untuk memberikan hak pendidikan tanpa terkecuali termasuk mereka yang memiliki perbedaan dalam kemampuan (difabel). Tujuan dilakukan penelitian ini yaitu untuk menganalisis implementasi program pendidikan anak berkebutuhan khusus (ABK), penelitian ini menggunakan metode kualitatif deskriptif, pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi, dari hasil penelitian yang di lakukan di SDLB Negeri prabumulih, ada beberapa jenis anak berkebutuhan khusus (ABK) yang memiliki klasifikasi yang berbeda, guru melakukan assesment setiap semester untuk mengidentifikasi anak berkebutuhan khusus (ABK). Sekolah ini menggunakan kurikulum 2013 dan kurikulum khusus saat di perlukan, dalam proses pembelajaran di kelas tidak berbeda jauh dengan sekolah umum lainnya, hanya saja terkadang guru harus lebih sabar dalam menghadapi siswa difabel (kemampuan yang berbeda atau abnormal)..Kata Kunci : Analisis, Poses pembelajaran, ABK